How does digital learning resource accessibility affects math learning anxiety in high school—an empirical analysis based on PISA 2022 - Wang, Cunkuan; Yang, Guizhen; Cui, Haoran; Ming, Yuelong; Sun, Zhendong (Frontiers in Psychology, 2025)
IntroductionAs math learning anxiety remains a persistent barrier to student achievement and well-being, it is crucial to understand how digital learning environments can alleviate or intensify this issue.MethodsDrawing on large-scale PISA 2022 survey data from high-school students, this study examines how the quality, usage frequency and manner of use of digital learning resources relate to students’ math learning anxiety, with teacher support and sense of school belonging tested as moderators.ResultsLinear regression analyses reveal that both the quality of digital learning resources and their manner of use are significantly associated with reduced math learning anxiety, whereas usage frequency shows no significant effect. Moderation analyses further indicate that teacher support consistently buffers the impact of all three dimensions of digital resource accessibility on math anxiety, while sense of school belonging only moderates the effects of quality and manner of use.DiscussionThese findings underscore the importance of ensuring high-quality digital resources, fostering supportive teacher–student interactions, and cultivating students’ sense of belonging to reduce math-learning anxiety. Limitations include the cross-sectional design and self-reported data; future longitudinal or experimental studies should test these patterns across contexts.